1975
DOI: 10.1159/000214092
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Trial of Platelet Anti-Aggregating Agents and Subcutaneous Heparin in Prevention of Postoperative Deep Vein Thrombosis in High Risk Patients

Abstract: In a prospective randomised trial, three groups of 20 patients each were compared. A first group served as a control, a second group received dipyridamole and acetylsalicylic acid and a third group received low doses of heparin. The incidence of deep vein thrombosis determined by the 125I-fibrinogen test was 40 % in the first group, 50 % in the second group, and 5 % in the third group. The differences between the heparin group and the two other groups are statistically significant. No wound complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…In the 1970s and 1980s, a number of studies investigated the use of aspirin in THA, 10,[62][63][64][65] TKA, 66 and HFS. [67][68][69][70][71][72] Those studies used high doses of aspirin of up to 3.8 g daily.…”
Section: Aspirin Vs No Prophylaxis-initial Plus Extended Prophylaxis mentioning
confidence: 99%
“…In the 1970s and 1980s, a number of studies investigated the use of aspirin in THA, 10,[62][63][64][65] TKA, 66 and HFS. [67][68][69][70][71][72] Those studies used high doses of aspirin of up to 3.8 g daily.…”
Section: Aspirin Vs No Prophylaxis-initial Plus Extended Prophylaxis mentioning
confidence: 99%
“…Thus far, four prospective randomized trials with aspirin have been published in orthopedic surgical patients [109,222,242,300] and three other reports are available in abstract from [108,117,164]. In addition, four other randomized trials have been published in which aspirin was combined with either RA 233 [287], or dipyridamole [54,178], or low-dose heparin [225], and another trial with the aspirin-dipyridamole combination has been published in abstract form [231]. All these trials were done with patients undergoing hip surgery, except for a preliminary report in which patients undergoing total knee replacement were under study [164].…”
Section: Prevention Of Venous Thromboembolism 711 General Surgery (mentioning
confidence: 99%
“…Three small randomized trials have compared a control group with either aspirin associated with RA 233 [287] or aspirin combined with dipyridamole [54,178] in patients undergoing surgery either for fracture of the femoral neck [178,287] or total hip replacement for osteoarthritis [54]. Prophylaxis was begun before surgery and diagnosis of deep vein thrombosis was determined with the 125 I-fibrinogen test.…”
Section: Aspirin Hemostasis and Thromboembolismmentioning
confidence: 99%
“…140 Administration of dipyridamole with aspirin has been reported to significantly decrease (p < 0.05) the incident of DVT after abdominal surgery.141.142 Significant (p < 0.05) benefit from the combination also has been reported in controlled studies of patients with recurring DVT and complete lower limb paralysis resulting from spinal cord compression.P-':" On the other hand, dipyridamole plus aspirin has been proven ineffective in preventing DVT after hip surgery. [144][145][146][147] Dipyridamole alone in doses :5400 mg/d has been shown, in controlled studies, to be ineffective in preventing DVT!46.148-150 In a study in which the efficacy of dipyridamole, aspirin, warfarin, and dextran were compared, only dipyridamole failed to provide significant (p < 0.05) benefit when compared with untreated controls.!" Also, since none of the studies that demonstrated a beneficial effect from dipyridamole plus aspirin included a group receiving aspirin only, dipyridamole may have added nothing to this treatment.…”
Section: Drug Intelligence and Clinical Pharmacy 1984 Nov Vol 18 873mentioning
confidence: 99%